Effective management of an information technology professional's career - Tedder, Derek (Rhodes University, Faculty of Commerce, Department of Information Systems, 2005)
The human resource is constantly cited as an organisation's greatest asset. In a rapidly changing technological environment this is most applicable to the Information Technology (IT) function. Organisations are experiencing IT human resource problems such as low satisfaction, early plateauing, high turnover, burnout, limited advancement potential, nominal corporate commitment, supervisory aversion, poor organisational culture, and exceptional compensation. These problems are directly related to the IT professional's career. There is a lack of information and awareness surrounding IT careers to deal effectively with these problems. The research aims to create increased awareness of IT careers and the inherent problems through the development of a career management model. The research aims to identify the factors that influence IT careers, provide career management with a means to measure compatibility of the factors, and suggest solutions to incompatibility. The solving of this problem will be of mutual benefit to both organisations and individuals as they seek to better manage IT careers. After reviewing research literature relating to career anchors, IT job types, IT skills portfolios, and career dynamics a model for Effective IT Career Management (EITCM) has been constructed. The model represents the dynamic interactions between individual, organisational, and dependent factors. The model examines the compatibility of these interacting factors by measuring the levels of relevant career variables. The model suggests appropriate career management techniques to increase the compatibility of the interacting factors. An empirical study was designed and launched online to provide data that would confirm the seven Critical Success Factors (CSF) relating to the proposed model. The responses from the members of the Computer Society of South Africa (CSSA) allowed the seven hypotheses derived from the CSFs to be tested. The results of the empirical study were positive but required modification to five of the CSFs before they could be confirmed. The EITCM model was modified to reflect the improved CSFs. An awareness of career influencing factors combined with active career management is advantageous to both IT professionals and their organisations.
Keywords: Information technology -- Vocational guidance; Information technology -- Management; Knowledge management; Career development; Computer Science -- Vocational guidance; System analysis -- Vocational guidance